Design and research of hybrid piezoelectric-electromagnetic energy harvester based on magnetic couple suction-repulsion motion and centrifugal action. (15th April 2022) - Zhou, Jianwen; He, Lipeng; Liu, Lei; Yu, Gang; Gu, Xiangfeng; Cheng, Guangming
Highlights: Suction-repulsion action of magnetic force complete energy harvester. Prototype increase the reliability of system compared with collision structure. Hybrid mechanism solves the power limitation problem and improves output power. Abstract: In this paper, a hybrid piezoelectric-electromagnetic energy harvester (HEH) based on magnetic couple suction-repulsion motion and centrifugal action is proposed. Using a control variable approach, the effect of two variables on the output performance was investigated under different parameter conditions in order to maximize the output power. At a mounting angle of 60 degrees for the piezoelectric cantilever beam and a mass of 3.2 g for the rectangular magnet, the entire piezoelectric-electromagnetic harvester can produce 13.32 mW of power, which can successfully power low-power electronic devices such as light-emitting diodes (LEDs) . The power generated by mixing piezoelectricity and electromagnetism is 1.16 times greater than the power generated by the piezoelectric generation unit alone and 70.1 times greater than the power generated by the electromagnetic generation unit alone. The composite piezoelectric-electromagnetic hybrid mechanism greatly increases the power output of the entire structure compared to the single generation mode. The suction-repulsion process is accomplished using magnetic coupling. This makes the piezoelectric cantilever beam deformed by the magnetic force and has power output. At the same time, the magnetic suction-repulsion makes the circular magnet complete cutting magnetic induction line motion at the same time, which cleverly combines piezoelectricity and electromagnetism. The form of reciprocating motion of the magnet in the coil frame using suction-repulsion is also proposed for the first time. In addition, compared with those structures that strike the piezoelectric cantilever to generate electricity, this paper uses magnetic coupling, which makes the piezoelectric cantilever beam more durable and longer in use. In summary, this structure has good prospects for application in the direction of powering wireless networks or low-power electronic devices.